Sexual reckonings : Southern girls in a troubling age - Cahn, Susan K. (Harvard University Press, 2007)
Sexual Reckonings is the fascinating tale of adolescent girls coming of age in the South during the most explosive decades for the region. Focusing on the period from 1920 to 1960, Susan Cahn reveals how both the life of the South and the meaning of adolescence underwent enormous political, economic, and social shifts.